ST-elevation in aVR with Diffuse ST-segment Depression: Need for Urgent Catheterization? - Bruce M. Lo; Megyn K. Christensen; Katherine E. Schaffer; Theodore J. Tzavaras (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: A 33-year-old female with a history of antiphospholipid syndrome presented with exertional chest pain and ST-elevation in aVR with diffuse ST-segment depression. An emergent catheterization was performed, which showed an isolated 99% stenosis in the left main coronary artery. The remaining coronary arteries were without any stenosis. Successful stent placement was performed, and the patient was discharged without complications. Discussion: Previous guidelines have suggested that ST-segment elevation with diffuse ST-segment depression should be treated as a ST-elevation myocardial infarction equivalent involving either the left-main or proximal left anterior descending coronary artery. However, recent data suggests that most of these cases may not involve that region. Regardless, this electrocardiogram finding should still be a concern for acute coronary syndrome, with the need for urgent catheterization.